Upaya Guru Meningkatkan Prestasi Dalam Pembelajaran PAI Pasca Masa Pandemi Covid-19 di SDN Pasir Tengah 02 - Muhamad Rifki Munawar (VISA: Journal of Vision and Ideas, 2023)
The impact of the Covid-19 outbreak caused students to experience learning boredom, thereby reducing student achievement during the learning process. Therefore teachers must strive to improve learning achievement, especially PAI learning at Pasir Tengah 02 State Elementary School during post-Covid-19 learning. The purpose of this research is to analyze the teacher's efforts and supporting factors in improving learning achievement in PAI learning after Covid-19. The method in this study uses a qualitative approach, namely a method for investigating objects that cannot be measured by words or other measures that do not use numbers. Qualitative research can also be interpreted as research that is descriptive in nature and tends to use analysis with an inductive approach. The results of this research are to improve learning achievement in PAI learning after Covid-19 including: providing examples of good behavior to students, managing classes well, repeating learning, fun learning methods, and conducting learning evaluations. And there are several supporting factors that help improve learning achievement in PAI learning after Covid-19 including: providing examples of good behavior to students, managing classes well, repeating learning. fun learning methods. and conduct learning evaluations. Keyword: Master's Efforts; Learning achievement; PAI learning